Evaluation of Victim Advocacy Services Funded by the Violence Against Women Act in Urban Ohio, 1999 - Bohmer, Carol ([Verlag nicht ermittelbar], 2000)
The focus of this research and evaluation endeavor was on direct service programs in Ohio, particularly advocacy services for female victims of violence, receiving funding through the Services, Training, Officers, Prosecutors (STOP) formula grants under the Violence Against Women Act (VAWA) of 1994. The objectives of this project were (1) to describe and compare existing advocacy services in Ohio, (2) to compare victim advocacy typologies and identify key variables in the delivery of services, (3) to develop a better understanding of how victim advocacy services are defined and delivered, and (4) to assess the effectiveness of those services. For Part 1, Service Agencies Data, comprehensive information about 13 VAWA-funded programs providing direct services in urban Ohio was gathered through a mailback questionnaire and phone interviews. Detailed information was collected on organizational structure, clients served, and agency services. Focus groups were also used to collect data from clients (Parts 3-11) and staff (Parts 12-23) about their definitions of advocacy, types of services needed by victims, services provided to victims, and important outcomes for service providers. Part 2, Police Officer Data, focused on police officers' attitudes toward domestic violence and on evaluating service outcomes in one particular agency. The agency selected was a prosecutor's office that planned to improve services to victims by changing how the police and prosecutors responded to domestic violence cases. The prosecutor's office selected one police district as the site for implementing the new program, which included training police officers and placing a prosecutor in the district office to work directly with the police on domestic violence cases. The evaluation of this program was designed to assess the effectiveness of the police officers' training and officers' increased access to information from the prosecutor on the outcome of the case. Police officers from the selected district were administered surveys. Also surveyed were officers from another district that handled a similar number of domestic violence cases and had a comparable number of officers employed in the district. Variables in Part 1 include number of staff, budget, funding sources, number and type of victims served, target population, number of victims served speaking languages other than English, number of juveniles and adults served, number of victims with special needs served, collaboration with other organizations, benefits of VAWA funding, and direct and referral services provided by the agency. Variables in Part 2 cover police officers' views on whether it was a waste of time to prosecute domestic violence cases, if these cases were likely to result in a conviction, whether they felt sympathetic toward the victim or blamed the victim, how the prosecution should proceed with domestic violence cases, how the prosecution and police worked together on such cases, whether domestic violence was a private matter, and how they felt about the new program implemented under VAWA.